Moral Consideration Regarding the Arizona Tax Credit Law - Rud, Anthony G. (Education Policy Analysis Archives, 2000)
I begin by commenting on the language used, both by the Arizona tax credit law, and by our commentators, and then turn to a discussion of a factor I believe fuels the impetus for sectarian education. I end with a consideration of questions related to the social, cognitive, and moral costs of such privatization, in contrast to a democratic commitment to education.